EKSISTENSI PANCASILA SEBAGAI LANDASAN PERTAHANAN NEGARA DALAM MENGHADAPI ANCAMAN IDEOLOGI ASING - Afdhali, Dino Rizka; Triadi, Irwan (Collegium Studiosum Journal, 2023)
A country is not always in a conducive and controlled state. Several disturbances and threats often occur which can threaten the integrity and sovereignty of the country. One of the threats to the state is ideology which can change the order of society and its perspective. In this era of globalization, Pancasila as a state ideology is being tested again by many foreign ideologies trying to enter our country through information media and technology that can be reached by all groups, such as the ideologies of communism, liberalism, capitalism, religious extremism and others. This journal aims to determine the existence of Pancasila as the basis for national defense in facing foreign ideological threats. The method used in this legal research is normative juridical legal research which uses library materials as primary sources. The results of this research are that even though it is often faced with interference and threats from foreign ideologies that want to replace the existence of Pancasila, the Pancasila ideology is able to continue to exist and is able to fight with other major ideologies which also act as a filter for foreign ideologies in influencing the Indonesian nation.